EALLU: Arctic Indigenous Youth, Arctic Change and Food Culture; Policy Recommendations, and Cookbook - Sustainable Development Working Group (SDWG) (Arctic Council Secretariat, 2017)
Over millennia, Arctic Indigenous Peoples' culinary traditions and food culture have nourished peoples, enriched communities, bound generations and embodied the very essence of 'sustainability'. This is ancient knowledge enacted in the everyday. Over millennia, Arctic Indigenous Peoples' culinary traditions and food culture have nourished peoples, enriched communities, bound generations and embodied the very essence of 'sustainability'. This is ancient knowledge enacted in the everyday.